Behaviour of CFST columns and their classification based on ductility factor and failure modes - Akilesh, R.; Peter, Minu Ann; Sajith, A.S.; Nagarajan, Praveen (Journal of Structural Engineering, 2024)
Composite columns such as Concrete-Filled Steel Tubes (CFST) are widely used in construction practice on accountof their improved ductile behaviour. This research work presents certain relevant aspects related to the behaviour ofcircular CFST columns under uniaxial compression. Load deformation, ductility factor and failure modes are studiedfor varying diameter (D) to thickness (t) and length (L) to diameter ratios. Initially, numerical modelling of the CFSTcolumns was carried out using commercially available finite element software and these were substantiated by carryingout experimental studies. The strength obtained were compared using Load and Resistance Factor Design (LRFD)specifications. Further experimental studies were carried out in two phases. In the first phase, the behaviour of fourCFST columns were compared to that of hollow steel tube columns for two different D/t ratios and four different L/Dratios. The second phase was an attempt to classify the CFST columns as short and slender columns based on thevariation of ductility factor and failure modes (for different D/t and L/D ratios). The results show that CFST columnsare more ductile than hollow steel tube columns. Variation of ductility factor was plotted based on D/t and L/D ratio.By observing the ductility factor, a limiting value of 15 was determined for D/t ratio. Also from the failure modes, it isobserved that a change from short column to slender column occur at an L/D ratio of 9. The load carrying capacity ofCFST columns were compared with LRFD specifications. The numerical and experimental values were found to showa variation of less than 10%.